Basic mechanisms of iron metabolism regulation and their clinical significance - L. M. Meshсheryakova; A. A. Levina; M. M. Tsybulskaya; T. V. Sokolova (Онкогематология, 2015)
This article is а composition of literature and experimental data of iron metabolism. There were studied the level of DMT-1, ferroportin, hepcidin at different stages of anemia and hemochromatosis. It is clear that the level of DMT-1 regulates by the hepcidin. Increaseing of the hepcidin concentration and decreasing DMT-1 level in patients with hemochromatosis explained good results of treatment.